Morphometric variations of laelapine mite (Acari: Mesostigmata) populations infesting small mammals (Mammalia) in Brazil - F. Martins-Hatano; Gettinger D; ML. Manhães; HG. Bergallo (Brazilian Journal of Biology)
The goal of this study was to evaluate the morphometric variation of laelapine populations (Acari, Mesostigmata) associated with neotropical oryzomyine rodents at different geographic localities in Brazil. Three nominal mite species were selected for study, all infesting the pelage of small mammals at different localities in Rio de Janeiro, Espírito Santo, Bahia, and the Federal District, Brazil. To analyse morphometric characteristics, thirty-seven morphological characters distributed across the whole body of each specimen were measured. We use the Analysis of Principal Components, extracting the three first axes and projecting each mite in these axes. Major species level changes in the taxonomy of the host mammals allows an independent examination of morphometric variation of mites infesting a set of distinctly different host species at different geographic localities. Gigantolaelaps vitzthumi and Laelaps differens are associated with oryzomyine rodents of the genus Cerradomys, and consistently showed a tendency to cluster by host phylogeny. Laelaps manguinhosi associated with Nectomys rattus in central Brazil is morphometrically distinct from mites infesting N. squamipes in the coastal restingas of Rio de Janeiro and Espírito Santo. The results obtained here indicate that laelapine mite populations can vary among geographic areas and among phylogenetically related host species. Clearly, the study of these mites at the population level can be an important tool for clarifying the taxonomy of both mites and hosts.